Efficient production of hydrogen by catalytic decomposition of methane with Fe-substituted hexaaluminate coated packed bed. (15th June 2023) - Dai, Huaming; Song, Ziwei; Wang, Hongting; Cui, Qingyuan
Abstract: Hydrogen as an ideal clean energy showed the advantages of high energy density and renewable utilization. Catalytic combustion in porous media was one of the efficient methods for partial oxidation of methane to produce hydrogen. In this paper, the LaFex Al12-x O19 catalyst was prepared to analyze its effects of metal substitution content and filling height on the temperature distribution, species concentration yield and energy conversion efficiency. Results indicated that with the increasing of Fe content, the active sites were greatly increased so that the catalytic performance of LaFe3 Al9 O19 was better than that of LaFeAl11 O19 . In addition, the catalytic burner with Fe substituting obtained higher axial temperature compared with the inert burner. At the inlet velocity of 18 cm/s, the methane conversion and hydrogen yield reached the highest of 99.2% and 58.5% for the LaFe3 Al9 O19 burner with the longest filling height. As the inlet velocity increased, the hydrogen production and H2 /CO promoted. Moreover, the higher equivalence ratio from 1.2 to 1.5 contributed to the syngas production and the reforming efficiency increased by 30.7%, but further increasing of equivalence ratio significantly weakened the partial oxidation of methane. The prepared hexaaluminate catalyst provided an important reference for the hydrogen production from the methane-containing gas. Graphical abstract: Image 1 Highlights: A double-layer burner impregnated with catalyst in the downstream section was designed. Alumina pellets were coated with hexaaluminate catalyst by co-precipitation method. Hydrogen production efficiency of methane was greatly improved by adding catalyst. Energy conversion efficiency increased with the increasing of inlet velocity.